Ammonia- and methane-oxidizing microorganisms in high-altitude wetland sediments and adjacent agricultural soils - Yang, Yuyin; Shan, Jingwen; Zhang, Jingxu; Zhang, Xiaoling; Xie, Shuguang; Yong Liu (APPLIED MICROBIOLOGY AND BIOTECHNOLOGY, 2014)
Ammonia oxidation is known to be carried out by ammonia-oxidizing bacteria (AOB) and archaea (AOA), while methanotrophs (methane-oxidizing bacteria (MOB)) play an important role in mitigating methane emissions from the environment. However, the difference of AOA, AOB, and MOB distribution in wetland sediment and adjacent upland soil remains unclear. The present study investigated the abundances and community structures of AOA, AOB, and MOB in sediments of a high-altitude freshwater wetland in Yunnan Province (China) and adjacent agricultural soils. Variations of AOA, AOB, and MOB community sizes and structures were found in water lily-vegetated and Acorus calamus-vegetated sediments and agricultural soils (unflooded rice soil, cabbage soil, and garlic soil and flooded rice soil). AOB community size was higher than AOA in agricultural soils and lily-vegetated sediment, but lower in A. calamus-vegetated sediment. MOB showed a much higher abundance than AOA and AOB. Flooded rice soil had the largest AOA, AOB, and MOB community sizes. Principal coordinate analyses and Jackknife Environment Clusters analyses suggested that unflooded and flooded rice soils had relatively similar AOA, AOB, and MOB structures. Cabbage soil and A. calamus-vegetated sediment had relatively similar AOA and AOB structures, but their MOB structures showed a large difference. Nitrososphaera-like microorganisms were the predominant AOA species in garlic soil but were present with a low abundance in unflooded rice soil and cabbage soil. Nitrosospira-like AOB were dominant in wetland sediments and agricultural soils. Type I MOB Methylocaldum and type II MOB Methylocystis were dominant in wetland sediments and agricultural soils. Moreover, Pearson's correlation analysis indicated that AOA Shannon diversity was positively correlated with the ratio of organic carbon to nitrogen (p < 0.05). This work could provide some new insights toward ammonia and methane oxidation in soil and wetland sediment ecosystems.